2015
DOI: 10.1115/1.4029275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Cavity Geometries on Machining Performance in Micro-Electrical Discharge Milling

Abstract: Low energy-short pulsed electric discharge coupled with precise movement of circular electrode in micro-electrical discharge-milling (μ-EDM-milling) enables generation of three-dimensional (3D) cavities in the order of few tens of microns. Use of unshaped rotating electrode alters the spark discharge pattern that is primarily driven by the shape and size of the cavities being machined. In this paper, effects of five different cavities: circular, triangular, square, channel, and cross channel (square pillars) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Discharge patterns and shape errors in micro-ED milling operation. 18 has been widely used as a dielectric fluid in WEDM, but many reported literature suggest that the use of EDM oil instead of deionized water produces better results while machining of hard materials such as single-crystal silicon, tungsten carbides and polycrystalline diamonds (PCDs). 24 Compared to water-based WEDM operations, oil-based WEDM could not only eliminate electrolysis and corrosion but also prevent cobalt depletion in the cutting of metal carbides and therefore achieve better surface morphology and surface finish.…”
Section: Variants Of Micro-edmmentioning
confidence: 99%
See 1 more Smart Citation
“…Discharge patterns and shape errors in micro-ED milling operation. 18 has been widely used as a dielectric fluid in WEDM, but many reported literature suggest that the use of EDM oil instead of deionized water produces better results while machining of hard materials such as single-crystal silicon, tungsten carbides and polycrystalline diamonds (PCDs). 24 Compared to water-based WEDM operations, oil-based WEDM could not only eliminate electrolysis and corrosion but also prevent cobalt depletion in the cutting of metal carbides and therefore achieve better surface morphology and surface finish.…”
Section: Variants Of Micro-edmmentioning
confidence: 99%
“…17 In this process, a cylinder-shaped tool rotates around the Z -axis, and it has its scanning movement in the X - and Y -directions. 18 During the micro-EDM milling method, a minimum spark gap is maintained ensuring that the tool and the workpiece do not touch each other. In this method, a very small holding force is applied to the workpiece, avoiding vibration and mechanical stress.…”
Section: Introduction To Conventional Edm and Micro-edm Processmentioning
confidence: 99%
“…Rossella Surace et al (2016) designed and fabricated a polymeric micro filter for the use in biomedical sciences with the aid of EDM [85].Tassilo-Maria Schimmelpfennig et al (2015) carried out comapritive study of wet and dry EDM and came out with result that dry EDM has lower ringing effect and need sensitive tool drive with micro-piezoelectric actuators [61]. Shrikant Vidya et al (2015) observed that in µEDM side discharge covering a segment of 120 deg around the cylindrical electrode attributes to tool deflection, non-uniform spark gap, and jumping of discharges and rotation of tool electrode benefits significantly [62]. Hamid studied the effect of rotation of electrode, powder addition and magnetic field simultaneously and found that with the addition of 1 g/l of TiO2 powder and application of magnetic field (0.38 T) could help to increase the MRR and also suggested that higher spark energy leads to conversion of large amount of electric energy to thermal energy and enhance MRR [63].…”
Section: Assorted Unprecedented Ideasmentioning
confidence: 99%
“…Molten metal ejected from the electrode can either flow as a secondary fluid or form globules which on subsequent cooling generates spherical particles or debris. [21][22][23] The size and shape of the globules depend on the discharge energy, crater size and amount of molten metal expelled. When the quantity of the expelled molten metal is larger, then it deposits on the nearby surface forming redeposited layer.…”
Section: Effect Of Iegmentioning
confidence: 99%